Amphotericin B Specifically Induces the Two-Component System LnrJK: Development of a Novel Whole-Cell Biosensor for the Detection of Amphotericin-Like Polyenes - Revilla-Guarinos, Ainhoa; Dürr, Franziska; Popp, Philipp F.; Döring, Maximilian; Mascher, Thorsten (Frontiers in Microbiology, 2020)
The rise of drug-resistant fungal pathogens urges for the development of new tools for the discovery of novel antifungal compounds. Polyene antibiotics are potent agents against fungal infections in humans and animals. They inhibit the growth of fungal cells by binding to sterols in the cytoplasmic membrane that subsequently causes pore formation and eventually results in cell death. Many polyenes are produced by Streptomycetes and released into the soil environment, where they can then target fungal hyphae. While not antibacterial, these compounds could nevertheless be also perceived by bacteria sharing the same habitat and serve as signaling molecules. We therefore addressed the question of how polyenes such as amphotericin B are perceived by the soil bacterium, Bacillus subtilis. Global transcriptional profiling identified a very narrow and specific response, primarily resulting in strong upregulation of the lnrLMN operon, encoding an ABC transporter previously associated with linearmycin resistance. Its strong and specific induction prompted a detailed analysis of the lnrL promoter element and its regulation. We demonstrate that the amphotericin response strictly depends on the two-component system LnrJK and that the target of LnrK-dependent gene regulation, the lnrLMN operon, negatively affects LnrJK-dependent signal transduction. Based on this knowledge, we developed a novel whole-cell biosensor, based on a PlnrL-lux fusion reporter construct in a lnrLMN deletion mutant background. This highly sensitive and dynamic biosensor is ready to be applied for the discovery or characterization of novel amphotericin-like polyenes, hopefully helping to increase the repertoire of antimycotic and antiparasitic polyenes available to treat human and animal infections.